Pesticide’s Dangers to Wildlife and Safeguard Dealings in Reducing of the Risks - Sarwar, Muhammad (International Journal For Research In Health Sciences And Nursing, 2016)
This paper addresses the effects of various pesticides on nontarget organisms including wildlife, fish and honeybees and safeguard dealings in reducing of risks. Pesticides are the only toxic substances released intentionally into environment to kill pests. This includes substances that kill weeds (herbicides), insects (insecticides), fungus (fungicides), rodents (rodenticides) and others. A side effect of usage of some pesticides results in unfortunate consequences to our nontarget organisms. Wildlife animals usually live in a natural environment including those hunted for food, sport or profit, especially mammals, birds, fishes, amphibians and aquatic insects that are neither human nor domesticated. Directly, wildlife can be exposed to pesticides by eating contaminated food or water, breathing pesticide spray or absorbing pesticides through their skin. Indirectly, predators such as hawks and others can become poisoned by eating other animals that have been exposed to pesticides. For the reason that many insecticides affect the nervous systems of wildlife, exposure to a particular insecticide can affect animals indirectly, by interfering with their ability to survive or reproduce. Before making a pesticide application, it is important to become familiar with the area to be treated and its surroundings. Some pesticides are more environmental friendly than others and may be selected for sites where there are special concerns, and choose a product that is least toxic to nontarget organisms. As with any pesticides application, take precautions with drift, evening or night is the safest time of day for applications, early morning would be fairly safe, and midday has the greatest potential for toxicity concerns. Bees are essential for pollination of many fruit crops that can be harmed by some pesticides used to manage insects, mites and diseases in fruit crops. Growers can reduce pesticide risk to bees through the approaches to develop and implement a pollination contract with beekeepers. Select the least toxic pesticides and formulations when possible, reduce drift onto areas outside crop fields, remove flowering weeds from crops and provide bee-friendly habitat away from crops. Use integrated pest management (IPM) to reduce the need for sprays, avoid pesticide sprays during crop bloom, apply pesticides after sunset or before sunrise, or when air temperature is below 50°F. Integrated pest management practices include using cultural controls, planting pest resistant varieties, scouting fields to monitor pest populations, biological control and using insecticides only when other control measures fail to keep pest numbers or damage below levels which cause economic crop loss.